Effect of Carica papaya Leaf Juice on Hematology of Mice (Mus musculus) with Anemia - Afreni Hamidah; Evita Anggereini; Nurjanah Nurjanah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Anemia is defined as a decrease in haemoglobin concentration and the number of erythrocytes. One source of iron in vegetable is the papaya leaf. This study aimed to determine the number of erythrocytes and hemoglobin levels after the application of Carica papaya leaf on mice through the sodium nitrite induction. The research design used was Randomized Design Complete by using five treatments with five repetitions on each treatment. The data measured in this study was number of erythrocytes and hemoglobin levels of rats before being given sodium nitrite, after being given sodium nitrite and after being given papaya leaf juice. The data obtained were analyzed statistically by using variance analysis (ANOVA), and the data that significantly different was then analyzed by Duncan Multiple Range Test (DMRT). The results showed that papaya leaf juice significantly affected the increase of erythrocyte number and hemoglobin level. The concentration that gives the best effect in increasing the number of erythrocytes is 50% papaya leaf juice concentration and 25% papaya leaf juice concentration which gives the best effect in increasing the hemoglobin content. Further, the findings can be used as baseline information for further scientific investigation for using papaya leaf as an alternative medicine in curing anemia disease and analyzing phytochemical, pharmaceutical and other biological activities on other plant or vegetable and to conducted further research by using female mice and pregnant female mice.